Nature Inspired Load Balancing Algorithms in a Cloud Computing Environment (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Cloud computingÂ is a general term for anything that involves delivering hosted services over the Internet, One of the primary issues in cloud computing is implementation of a novel load balancing approach. The demanding thirst for optimal performance of the system is creating research interest in this area. Many Load Balancing algorithms that aim to enhance the overall system performance have been proposed. In this paper, we survey a special group of Load balancing algorithms that have taken inspiration from nature. We provide an overview of the current trends in the field by discussing and comparing these algorithms.